The New Proof of Euler's Inequality Using Spieker Center - Dasari Naga Vijay Krishna (International Journal of Mathematics And its Applications, 2015)
If R is the Circumradius and r is the Inradius of a non-degenerate triangle then due to EULER we have an inequality referred as Euler's Inequality which states that $R≥ 2r$, and the equality holds when the triangle is Equilateral. In this article let us prove this famous inequality using the idea of Spieker Center.